2001
DOI: 10.2136/sssaj2001.65167x
|View full text |Cite
|
Sign up to set email alerts
|

Residence Time Effects on Arsenate Adsorption/Desorption Mechanisms on Goethite

Abstract: In order to make sound decisions regarding arsenate contamination rish, 1979, 1983; Jacobs et al., 1970). Arsenate sorption in soil and water environments, it is necessary to have a thorough understanding of the mechanisms of arsenate sorption and desorption on soils and soil components vs. pH increases until maxiover extended periods. The major objectives of this study were to mum sorption is reached and then sorption decreases determine the effects of aging or residence time on the kinetics of with further p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
154
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(180 citation statements)
references
References 51 publications
23
154
0
Order By: Relevance
“…After 840 h the total desorption ratio reached about 50% and 41% for the samples with the sorption equilibrium time of 24 h and 840 h, respectively. The results indicate that a significant amount of As(V) was still retained in the soil even after 840 h of desorption since the phosphate added was three times higher than the initial As(V) concentration for the sorption experiments, which is in agreement with the observations of O'Reilly et al (2001).…”
Section: Kinetics Of Arsenate Sorption and Desorption In The Presence Ofsupporting
confidence: 88%
See 2 more Smart Citations
“…After 840 h the total desorption ratio reached about 50% and 41% for the samples with the sorption equilibrium time of 24 h and 840 h, respectively. The results indicate that a significant amount of As(V) was still retained in the soil even after 840 h of desorption since the phosphate added was three times higher than the initial As(V) concentration for the sorption experiments, which is in agreement with the observations of O'Reilly et al (2001).…”
Section: Kinetics Of Arsenate Sorption and Desorption In The Presence Ofsupporting
confidence: 88%
“…The two-stage sorption kinetics observed in this experiment was similar to the results for As(V) sorption on goethite reported by O'Reilly et al (2001). In the presence of oxalate or HA, As(V) sorption within 24 h was decreased by 34.6% and 36.2%, respectively, for the samples with the initial As(V) loading of 0.2 mM.…”
Section: Kinetics Of Arsenate Sorption and Desorption In The Presence Ofsupporting
confidence: 88%
See 1 more Smart Citation
“…1), would have been adsorbed mainly onto the surface hydroxyl groups at layer silicate edges, onto oxyhydroxides of Fe and Al, and onto non-crystalline aluminosilicates. It has been suggested that the adsorption mechanisms of arsenate are similar to those of phosphate (Fendorf et al 1997;O'Reilly et al 2001). Thus, these AAs would be chemisorbed by variablecharge minerals to make inner-sphere complexes by ligand exchange reactions as well as by phosphate sorption (Obihara and Russell 1972;Nanzyo and Watanabe 1981).…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Furthermore, sorption of As(V) on soil minerals depends on the residence time, which has been attributed to different sites of reactivity, surface nucleation-precipitation or diffusion into micropores of the sorbent (Sparks 1999). Several kinetic studies have shown that the sorption rate of As(V) on Fe/Al oxide minerals and WTR was initially rapid, but was followed by a slower phase (Raven et al 1998;O'Reilly et al 2001;Makris et al 2006). Sarkar et al (2007) observed linear As(V) sorption by WTR (without soil) for different As(V) loads (ranging from 225 to 7,500 mg As kg -1 WTR) but proceeded slower thereafter, reaching 100 % after 48 h. There were numerous studies conducted on the effects of soil/solution chemistry on As(V) sorption by pure hydroxides, soils, and WTR (no soil) systems; to the best of our knowledge, no work has been conducted to investigate the effect of soil solution chemistry on As(V) sorption in WTR-amended soils.…”
Section: Introductionmentioning
confidence: 99%